Urothelial carcinoma: Perioperative considerations from top to bottom - Wesley Yip; Salvador Jaime‐Casas; Anjaney Kothari; Mary Sullivan; Leslie K. Ballas; Domenique Escobar; Anne K. Schuckman; Jonathan E. Rosenberg; Jonathan A. Coleman (CA: A Cancer Journal for Clinicians, 2025)
Abstract Urothelial carcinoma is an aggressive entity that is associated with significant morbidity, but there have been major advances in both our understanding of and treatment options for patients with this disease. In this review, the authors focus on novel therapeutic and diagnostic approaches in the perioperative setting, with an emphasis on patient‐centered and individualized care. For urothelial carcinoma of the bladder (UCB), advances in nonplatinum‐based therapies, specifically immunotherapy and antibody–drug conjugates, have expanded the therapeutic arsenal for patients with muscle‐invasive UCB in both the neoadjuvant and adjuvant settings to improve survival outcomes. Given the significant morbidity of extirpative surgery (radical cystectomy and urinary diversion), there have also been greater efforts to evaluate bladder‐sparing protocols and improve the selection of patients for surgery and their postoperative recovery. The authors review special considerations for organ‐sparing surgery in females, geriatric co‐management, and enhanced recovery after surgery protocols. For upper tract urothelial carcinoma, there has been increasing recognition of its unique diagnostic and therapeutic challenges, including risks of renal functional loss. There have been advances in molecular profiling that have demonstrated various genomic differences between upper tract urothelial carcinoma and UCB, with treatment implications. This article reviews studies evaluating perioperative care that focused on optimizing therapeutic approaches, including neoadjuvant/adjuvant chemotherapy and immunotherapy, as well as nephron‐sparing strategies in carefully selected cases.